2017
DOI: 10.1590/1678-4685-gmb-2016-0118
|View full text |Cite
|
Sign up to set email alerts
|

The plant cell cycle: Pre-Replication complex formation and controls

Abstract: The multiplication of cells in all living organisms requires a tight regulation of DNA replication. Several mechanisms take place to ensure that the DNA is replicated faithfully and just once per cell cycle in order to originate through mitoses two new daughter cells that contain exactly the same information from the previous one. A key control mechanism that occurs before cells enter S phase is the formation of a pre-replication complex (pre-RC) that is assembled at replication origins by the sequential assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 120 publications
(234 reference statements)
2
19
0
Order By: Relevance
“…In the HPT dataset we found exclusively upregulated ORC5, ORC6, CDC6, CDT1 (b), SLD5, POLE1, RFC1 and RPA1; additionally PSF1 and PCNA1, which are downregulated. In HTT we found exclusively upregulated genes including ORC2, MCM3, MCM4, MCM5, MCM7, MCM10, TOPBP1 (MEI1), POLA3, POLA4, POLD1, POLD3, RFC2, RFC3, RFC4, RPA1, RPA2 and RPA3 25,51 . POLA2 lays down a short RNA/DNA primer in the lagging strand synthesis 25 , and is upregulated in both HPT and HTT datasets.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…In the HPT dataset we found exclusively upregulated ORC5, ORC6, CDC6, CDT1 (b), SLD5, POLE1, RFC1 and RPA1; additionally PSF1 and PCNA1, which are downregulated. In HTT we found exclusively upregulated genes including ORC2, MCM3, MCM4, MCM5, MCM7, MCM10, TOPBP1 (MEI1), POLA3, POLA4, POLD1, POLD3, RFC2, RFC3, RFC4, RPA1, RPA2 and RPA3 25,51 . POLA2 lays down a short RNA/DNA primer in the lagging strand synthesis 25 , and is upregulated in both HPT and HTT datasets.…”
Section: Resultsmentioning
confidence: 91%
“…The pre-RC is a very important part of the cell cycle as it defines the origins to initiate DNA replication, regulates DNA replication and assures that each daughter cell receives identic DNA copies 51 . Pre-RC members are conserved in all eukaryotes and previous studies have shown that plants core DNA replication machinery is more similar to vertebrates than single celled yeasts 2527 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Entry into S phase, when DNA is replicated, is one of the most highly regulated events in the cell cycle. A prerequisite for DNA replication is binding of CDC6 to replication origins, which can only occur during G1, when CDK activity is at its lowest (Castellano et al, 2004;Brasil et al, 2017). However, DNA replication cannot begin until CDK levels rise at the G1/S transition, thus preventing rereplication of origins after S has begun.…”
mentioning
confidence: 99%